1992
DOI: 10.1111/j.1432-1033.1992.tb17107.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidnece that rat liver mitochondrial and cytosolic fumarases are synthesized from one species of mRNA by alternative translational initiation at two in‐phase AUG codons

Abstract: Rat liver contains two isozymes of fumarase, mitochondrial and cytosolic enzymes. Recently, we suggested that the precursors of both isozymes might be synthesized by one species of mRNA [Suzuki, T., Sato, M., J . Biol. Chem. 264, 2581-25861. To examine this possibility, we have isolated and characterized rat genomic clones for fumarase. The isolated clones covered almost all of the 5' half of the fumarase gene consisting of five exons. The first exon contained the whole 5' non-coding region and the signal pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

1994
1994
2001
2001

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…A different type of regulation has been described for the yeast genes encoding isopentenyl pyrophosphate:tRNA isopentenyltransferase (MODS) and ATP(CTP):tRNA nucleotidyltransferase (CCA1) and the rat fumarase gene (Suzuki et al, 1992). In the case of MODS, two transcripts are synthesized, and both contain two in-frame AUG codons in the 5' region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A different type of regulation has been described for the yeast genes encoding isopentenyl pyrophosphate:tRNA isopentenyltransferase (MODS) and ATP(CTP):tRNA nucleotidyltransferase (CCA1) and the rat fumarase gene (Suzuki et al, 1992). In the case of MODS, two transcripts are synthesized, and both contain two in-frame AUG codons in the 5' region.…”
Section: Discussionmentioning
confidence: 99%
“…The CCA7 gene and the rat fumarase genes also have heterogenous transcription start sites leading to mRNAs carrying two or three in-frame 5'AUG codons (Suzuki et al, 1992;Wolfe et al, 1994). For both genes, the most active AUG in terms of translation initiation appears to be the downstream one, despite the presente of one or two upstream AUG codons.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, although until recently it was assumed that multiple isoforms of an enzyme located in different compartments were encoded by separate nuclear genes, as is the case for superoxide dismutase (33) and malate dehydrogenase (34), examples of proteins targeted to more than one location are becoming more common. For example, the mitochondrial and cytosolic isoforms of rat fumarase (35) and isopentenyl-pyrophosphate:tRNA isopentenyltransferase and ATP(CTP):tRNA nucleotidyltransferase from yeast (36) are each the products of a single gene, as are the cytosolic and mitochondrial forms of alanine aminoacyl-tRNA synthetase in Arabidopsis (37). Analysis of transcription start sites in the latter gene showed the presence of two potential AUG codons in some transcripts, suggesting the possibility that the same message could give rise to two different polypeptides.…”
Section: Origin Of the Additional 38-kda Band After Protease Treatmenmentioning
confidence: 99%
“…They suggested that these transcripts encode two fumarase products, one harboring a mitochondrial signal peptide and the other lacking this sequence, thereby encoding a cytosolic protein. In rat liver Tuboi and colleagues (15) proposed that the transcript of the single fumarase gene can be translated from two in-frame AUGs thereby giving rise to two products, one harboring and one lacking a mitochondrial signal peptide. Importantly both of the above alternative models of distribution predict the existence of two fumarase primary translation products.…”
mentioning
confidence: 99%